2010
DOI: 10.1007/s10880-010-9197-0
|View full text |Cite
|
Sign up to set email alerts
|

National Survey of Psychologists’ Training and Practice in Breaking Bad News: A Mixed Methods Study of the MUM Effect

Abstract: Research on breaking bad news has involved undergraduates, medical students, and physicians. However, to date, no studies have examined how, or whether, psychologists are trained to break bad news, as well as their current practice of breaking bad news. This mixed methods study explored the training and practice of 329 licensed psychologists/APA members in breaking bad news, using the MUM effect as a theoretical backdrop. Results suggest (1) psychologists are, as hypothesized, significantly more reluctant to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
1
4
0
1
Order By: Relevance
“…This finding has practical implications for those who routinely deliver bad news. For example, health care providers experience anxiety when having to deliver bad news to a client, and this anxiety drives much of the reluctance to share the news (Merker, Hanson, & Poston, 2010). Consistent with this finding, our data also showed that messengers feel more reluctance when they themselves are the locus (H2).…”
Section: Discussionsupporting
confidence: 81%
“…This finding has practical implications for those who routinely deliver bad news. For example, health care providers experience anxiety when having to deliver bad news to a client, and this anxiety drives much of the reluctance to share the news (Merker, Hanson, & Poston, 2010). Consistent with this finding, our data also showed that messengers feel more reluctance when they themselves are the locus (H2).…”
Section: Discussionsupporting
confidence: 81%
“…Doctors and medical students have confessed that they encountered difficulties during truth telling . They felt psychological distress when telling bad news , which may have negatively impacted their emotional well‐being and work satisfaction. Most doctors (86%) indicated that they urgently needed clinical guidelines for truth telling , and 57–81% of doctors suggested the need for relevant in‐service education .…”
Section: Introductionmentioning
confidence: 99%
“…While not all evaluations that include assessment (e.g., forensic evaluations) are followed with a formal feedback session, this should be explained to a client in advance (APA, 2013). It is unacceptable not to provide feedback because of anxiety about presenting “bad news” to clients (Merker et al, 2010) or not wanting to provide feedback about invalid test performance (Carone et al, 2010).…”
Section: Provision Of Feedbackmentioning
confidence: 99%